Understanding Employee Brand Trust and Internal Brand Communications & Training (BCT) Effects on Employee Brand Performance: A study of the banking industry - Shoaib Muhammad; Salniza Salleh; Maha Mohammed Yusr (Goodwood Publishing, 2020)
Purpose: The present study aims to examine the impact of key internal branding practices on affective brand commitment (AC) and employee brand performance (EBP) in the financial services industry. Also assessed was the mediating role of AC in the relationship of brand trust, brand communication and training (BCT), and EBP. Research Methodology: A quantitative survey tool was employed to gather data from 426 respondents from public-sector banks in Pakistan. The sampling methods used were a combination of proportionate random and convenience sampling techniques. The partial least squares-structural equation modelling (PLS-SEM) was used to analyze and interpret the data. Results: Findings indicate that the relationship of brand trust, BCT and EBP was mediated by AC. Brand trust and BCT results in higher levels of bank staff’s AC; this employee affective attachment to the bank brand drive them to engage in brand supporting behaviors, which in turn, foster employee brand performance. Limitations: This study is limited by scope as only public sector banks were studied, which may not be sufficient to make an inference. Contribution: BCT and trust are critical drivers fostering EBP and brand success; however, AC in the relation ensures EBP remains either the same or higher in the long run. Hence, banking, and other service firms should focus on improving EBP to develop a strong and successful corporate brand. Keywords: Brand commitment, Internal brand communications, Brand training, Internal branding, Perceived organizational support (POS),Brand performance, Public Banks, IPMA analysis.